Persuratan Baru: An Alternative Paradigm to Western Literary Methodologies - Mohd. Tahir, National University of Malaysia (UKM), Ungku Maimunah (Asiatic: IIUM Journal of English Language and Literature, 2015)
As an ex-colony of Britain, the Malay literary world exhibits an intellectual rush to imbibe Western literary constructs at the expense of local literary tradition which, informed by Islam, has spanned centuries. These Western constructs, which contradict both Malay culture and Islam, the religion of the Malays, give rise not only to confusion of knowledge and epistemology (in particular the concept of literary function and aesthetics), but also reinvent new values and structures of literary form and practice. Malay literature thus takes on an unmistakably Western hue and identity. In the face of this foreign onslaught, local scholars feel an urgent need to revive analytical frameworks that are cognisant of Islamic precepts and Malay cultural dynamics. This is seen as a means to bring back to Malay literature the Islamic worldview and identity which have been eclipsed, and, in some cases, jettisoned altogether. One such framework is Persuratan Baru (Genuine Literature) or PB which is informed by the concept of taklif, principally accountability to God through observation of the syariah or Islamic jurisprudence. Persuratan Baru re-orientates Malay creative and critical writings by challenging the primacy of the story as the lynchpin of fiction. In its place, PB prioritises knowledge as the main organising principle of narrative on the one hand, and stylisation of ideas, with discourse positioned as a crucial tool of articulation, as an integrated method of foregrounding ideas in creative terms, on the other.